La Œubeïta et autres fantasmes animaliers chez les écrivains judéo-tunisiens francophones de l’entre-deux-guerres - Dugas, Guy (Ponti/Ponts, 2021)
Judeo-Maghrebian literature during interwar years, which represents the expression of a collective imagination inheriting the dhimma and hostage of the colonial relationship, is a somber, troubled literature. This aspect is reflected by the style and the themes adopted in this literary production. The article aims to show the presence – in this nowadays forgotten literature – of aggressive phantoms which express themselves in the darkest fantastic mode through a collection of terrifying creatures: the essay introduces some of those nocturnal creatures – especially the Œbeïta, the most popular ones –, born from an obsessively gloomy and overshadowed imagination. This paper is mainly about the works of Véhel, Ryvel and Danon.